Effektivitas Taklim Remaja Islam Masjid dalam Membentuk Karakter Remaja di Era Industri 4.0 di Masjid Riyadus Sholihin - Amrizal, Amrizal; Subandi, Subandi; Fadillah, Muhammad Kharis (CV. Creative Tugu Pena, 2020)
Morals for Muslims has been a very important factor in building true humanity, because morals shape human beings who are always obedient to Allah SWT and Prophet Muhammad SAW. This article was to analyze the effectiveness of RISMA (Remaja Islam Masjid) Taklim in Forming the Character of Youth in the Industrial Era 4.0 of Riyadus Sholihin. The researchers used field research method. The result showed that the understanding of RISMA of Riyadus Sholihin was effective in Industrial Era 4.0. All of them were wisely proven in optimizing their application of social media wisely. The role of taklim gave an impact for adolescent characters because they taught how to well behave into adolescents who have a good morals. Keywords: Morals in Industrial Era 4.0, RISMA in Industrial Era 4.0